2019
DOI: 10.1109/access.2019.2921894
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Robust Reversible Watermarking Scheme for Protecting Authenticity and Integrity of Medical Images

Abstract: It is of great importance in telemedicine to protect authenticity and integrity of medical images. They are mainly addressed by two technologies, which are region of interest (ROI) lossless watermarking and reversible watermarking. However, the former causes biases on diagnosis by distorting region of none interest (RONI) and introduces security risks by segmenting image spatially for watermark embedding. The latter fails to provide reliable recovery function for the tampered areas when protecting image integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 32 publications
1
89
0
Order By: Relevance
“…Especially when the scaling factor is as low as 0.1, its watermark can still be fully extracted with the NC value 1.0, which performs much better than other algorithms. In addition, in the comparison results of the downward translation, as shown in figure 31(g), the NC value of the proposed algorithm is slightly higher than the algorithm proposed by Liu et al [13] and Loan et al [18] When the downward translation exceeds 13%, the algorithm proposed in literature [13] and [18] are slightly higher than our algorithm after moving downwards by 15% and 20%, respectively. From the analysis of the introduction, the algorithm proposed by Loan et al [18] embedded the watermark by pre-selecting and setting the difference of the IF coefficient and its range, which effectively managed the IF coefficient of the image and enabled it to perform well in the downward translation.…”
Section: Comparisonmentioning
confidence: 52%
See 4 more Smart Citations
“…Especially when the scaling factor is as low as 0.1, its watermark can still be fully extracted with the NC value 1.0, which performs much better than other algorithms. In addition, in the comparison results of the downward translation, as shown in figure 31(g), the NC value of the proposed algorithm is slightly higher than the algorithm proposed by Liu et al [13] and Loan et al [18] When the downward translation exceeds 13%, the algorithm proposed in literature [13] and [18] are slightly higher than our algorithm after moving downwards by 15% and 20%, respectively. From the analysis of the introduction, the algorithm proposed by Loan et al [18] embedded the watermark by pre-selecting and setting the difference of the IF coefficient and its range, which effectively managed the IF coefficient of the image and enabled it to perform well in the downward translation.…”
Section: Comparisonmentioning
confidence: 52%
“…To further verify the robustness of the proposed algorithm, the standard brain volume data provided by matlab R2019b was used for a simulation comparison test. We compare the proposed algorithm with the anti-salt-and-noise-resistant brain magnetic resonance image watermarking method proposed by Mousavi et al [8], the robust watermarking scheme using coefficient difference and chaotic encryption proposed by Loan et al [18], and the reversible watermarking scheme based on recursive jitter modulation (RDM) proposed by Liu et al [13] Some data results are shown in table 11, and their detailed comparison performance are shown in Fig. 31.…”
Section: Comparisonmentioning
confidence: 99%
See 3 more Smart Citations